(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Attention Deficit Hyperactivity disorder (ADHD) occurs in 1 out of 20 modern children and adolescents. The article considers new diagnostic criteria for ADHD according to the American statistical classification of mental disorders DSM-V, which contains the following main changes: the age of manifestation is up to 12 years; the requirement for cross — situational character of symptoms is strengthened; the age dynamics of ADHD is reflected and a threshold number of symptoms is introduced for adult patients; comorbidity with autism spectrum disorders is allowed. The features of the survey of children and adolescents with ADHD are discussed. Treatment of the syndrome should be comprehensive and include methods of behavior correction, psychotherapy, and neuropsychological correction. Drug therapy requires sufficient duration, since the improvement of the condition should extend not only to the main manifestations of ADHD, but also to the socio-psychological side of patients ’ lives. A study of a group of children with ADHD showed that during long-term treatment with hopantenic acid, treatment periods of at least 4-6 months are necessary to overcome not only the main symptoms, but also disorders of adaptation and socio-psychological functioning (improving self-esteem, communication with others, and social activity). The development and application of comprehensive correction for ADHD should be carried out in a timely manner and should be individual in nature.